Formulation and Pharmaceutical Quality Evaluation of Tablets Containing Extract of Cinnamomum burmannii BARK and Colocasia esculenta (L) Schott Leaves - Erni Rustiani; Rina Agustina; Septia Andini (Jurnal Mandala Pharmacon Indonesia, 2023)
Cinnamon bark (Cinnamomum burmannii) is used traditionally and has an ingredient containing cinnamic acid compounds. Colocasia esculenta (L) Schott leaves contains of flavonoids, alkaloids, tannins, saponins, steroids, and terpenoids. Both of the plants C. esculenta and C. burmannii plants have the potential as anti-diabetics because they can lower blood glucose levels. This study aims to make combination tablets of C. burmannii bark and C. esculenta leaves extract with various concentrations of PVP K30 binder. This research made four formulas with the concentration of PVP K30, namely F1 (2%), F2 (3%), F3 (4%), and F4 (5%). Tablet preparations were prepared by the wet granulation method. Tablet analysis used flavonoids quercetin and cinnamic acid as markers. The results showed that the tablets were flat, round in shape, light green, had a slightly bitter taste, and had a distinctive aromatic odor. The differences in the concentration of PVP K30 binder 2-5% could affect the hardness, friability, disintegration time, and tablet dissolution (p<0.05). The tablet's hardness was 3.65-5.01 KP; friability was 0.705%, disintegration time was <15 minutes, and dissolution was 84.61% in 40 minutes. The levels of the flavonoid quercetin in the tablets were 4.21% and 8.03% cinnamic acid. A tablet combination of C. burmannii bark and C. esculenta leaves extract with a PVP K30 concentration of 5% (F4) has the best quality.